The role of regulatory system in ensuring halal compliance among poultry firm operators in Malaysia - Hashim, Husna; Saad, Norma; Khalid, Haniza; Laluddin, Hayatullah; , (Springer, 2018)
Chicken meat is the main protein diet among Malaysian. Malaysia's per capita consumption of poultry meat above 40 kg per year (Department of Statistics Malaysia), among the highest in the world. Halal compliance in the poultry industry is a very crucial issue to be dressed since many incident of non-compliance has been reported which rendered the Halal status of chickens in the market being questioned. For instance, in 2013 three poultry slaughtering and processing firms in Kuala Lumpur with capacity of producing 26 thousand chickens per day were found committing serious misconduct and slaughtering, processing and sanitation, where Halal status of this chicken meat were in doubt.